2008
DOI: 10.1161/circresaha.108.173682
|View full text |Cite
|
Sign up to set email alerts
|

Adventitial Mast Cells Contribute to Pathogenesis in the Progression of Abdominal Aortic Aneurysm

Abstract: Abstract-Abdominal aortic aneurysm (AAA) is histologically characterized by medial degeneration and various degrees of chronic adventitial inflammation, although the mechanisms for progression of aneurysm are poorly understood. In the present study, we carried out histological study of AAA tissues of patients, and interventional animal and cell culture experiments to investigate a role of mast cells in the pathogenesis of AAA. The number of mast cells was found to increase in the outer media or adventitia of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
154
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 148 publications
(162 citation statements)
references
References 43 publications
7
154
0
1
Order By: Relevance
“…Circulating mast cell precursor has been reported to mature in tissues by SCF (Zsebo et al 1990) and other cytokines such as IL-4 (Conti et al 2003;Yanagida et al 1995). In accordance with the report (de Paulis et al 1999), we have shown that the immunoreactivity of SCF was detected in the cytoplasm of mast cells (Tsuruda et al 2008), suggesting autocrine or paracrine regulation of differentiation and maturation of cells in aortic tissues. Schönbeck et al (2002) showed the augmented expressions of IL-4 and IL-10 in inflammatory cells of AAA tissues.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Circulating mast cell precursor has been reported to mature in tissues by SCF (Zsebo et al 1990) and other cytokines such as IL-4 (Conti et al 2003;Yanagida et al 1995). In accordance with the report (de Paulis et al 1999), we have shown that the immunoreactivity of SCF was detected in the cytoplasm of mast cells (Tsuruda et al 2008), suggesting autocrine or paracrine regulation of differentiation and maturation of cells in aortic tissues. Schönbeck et al (2002) showed the augmented expressions of IL-4 and IL-10 in inflammatory cells of AAA tissues.…”
Section: Discussionsupporting
confidence: 93%
“…More importantly, we demonstrated that the cell number was significantly increased at the outer media and adventitia of AAA, compared with either the early or advanced stage of atherosclerosis. The proportion of activated mast cells (seen as "degranulation") has been reported to be frequently observed in the adventitia of AAA compared to in advanced atherosclerosis (15±2 % vs. 0.4±0.3% total number of mast cells) (Tsuruda et al 2008). Thus, mast cells distributed "outside of aortic wall" appear to be associated with the AAA pathogenesis.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations